Nigeria’s Sugar Industry: Challenges, Opportunities, and Prospects for Self-Sufficiency - BASSEY, DR (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
The sugar industry in Nigeria is relatively young, having been established in the 1960s. However, it has not yet reached its full potential, as it currently only supplies about 5% of the country’s sugar demand. This lack of performance has led to the loss of foreign exchange earnings and hundreds of thousands of employment opportunities. The Nigerian Sugar Master Plan (NSMP) predicts that the country’s sugar demand will exceed 1.7 million metric tonnes by 2020, and to meet this demand, the country needs to establish 28 sugar factories and cultivate 250,000 hectares of land for sugarcane over the next 10 years. Private investors will provide most of the investment capital. The government has enacted various policy instruments, including fiscal incentives, tariffs, and the Backward Integration Program (BIP), to create a conducive policy environment for the sugar industry’s development. The Sugar Levy will also fund research and development studies and essential infrastructure. These policies aim to attract new investors and protect existing and new investments in the sugar sector. The approval of the NSMP and the adoption of the conducive policy environment demonstrate the government’s commitment to revitalizing the sugar industry and making it a crucial part of the nation’s industrial landscape. This paper highlights the progress made in the first ten years of the NSMP’s BIP, the establishment of the Nigeria Sugar Institute, and the expected increase in sugar production in NSMP phase II.